2000
DOI: 10.1007/s007050070007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of Helicoverpa armigera single-nucleocapsid nucleopolyhedrovirus

Abstract: The genome organization of the Helicoverpa armigera single-nucleocapsid nucleopolyhedrovirus (HearNPV) was investigated and compared to that of other baculoviruses. A detailed physical map was constructed for the restriction enzymes BamHI, BglII, EcoRI, HindIII, KpnI, PstI, SacI and XhoI. The 130.1-kilobase pairs (kb) long viral genome was cloned as restriction fragments into a plasmid library, which covered 97.5% of the viral genome. From this plasmid library about 45 kb of dispersed sequence information was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 25 publications
7
74
0
1
Order By: Relevance
“…These results are in line with data from previous studies performed with different variants of HearSNPV, in which variants of similar pathogenicities presented marked differences in speed of kill (36,50). Generally, the fastest-killing variants tend to produce lower numbers of OBs in each infected insect, because insects die faster and feed and grow less during the incubation period of infection, and the virus has less time to replicate (50)(51)(52)(53). However, we observed that HearLB1 was highly productive, despite being one of the fastestkilling variants.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with data from previous studies performed with different variants of HearSNPV, in which variants of similar pathogenicities presented marked differences in speed of kill (36,50). Generally, the fastest-killing variants tend to produce lower numbers of OBs in each infected insect, because insects die faster and feed and grow less during the incubation period of infection, and the virus has less time to replicate (50)(51)(52)(53). However, we observed that HearLB1 was highly productive, despite being one of the fastestkilling variants.…”
Section: Discussionsupporting
confidence: 90%
“…As protein-coding sequences are under strong evolutionary constraint, the average level of amino acid identity between proteins shared by two genomes appears to be a robust measure of the whole-genome level of relatedness between the species being compared. This level of identity was found to be relatively low for particular pairs of Alphabaculovirus species, exemplified by HearSNPVG4-BmNPV and LyxyMNPV-AcMNPV, which exhibit 41% and 33% amino acid identity, respectively [77] [44]. In addition, a high variability in GC content and gene number (ranging from 118 to 169 genes) across Alphabaculovirus genomes, a relatively low proportion of homologous genes shared by all alphabaculoviruses (among them are 37 core and 14 Alphabaculovirus-specific genes) compared to the entire gene content of each genome [9], and a large number of rearrangements in the genomes of particular alphabaculoviruses [78] suggest that the Alphabaculovirus genus includes highly diverged species.…”
Section: Originality Of the Cnementioning
confidence: 96%
“…EcoRI-K was cloned into the pTZ19R vector (Gibco-BRL) and denoted as plasmid pCXW125 (Chen et al, 2000). The chitinase ORF and its flanking regions were sequenced in both directions by primer walking (Sanger et al, 1977).…”
Section: Cloning and Sequencing Of The Hasnpv Chitinase Genementioning
confidence: 99%